Decrease in late presentation for HIV care in Kinshasa, DRC, 2006–2020 - Nadine Mayasi Ngongo (AIDS Research and Therapy, 2021)
Abstract Introduction Late presentation for HIV care is a well-described issue for the success of ART outcomes and the cause of higher morbidity, mortality and further transmission. Monitoring the level of late presentation and understanding the factors associated with it would help to tailor screening and information strategies for better efficiency. We performed a retrospective cohort study in Kinshasa, the capital of the DRC. The studied population included HIV-positive adults newly enrolled in HIV care between January 2006 and June 2020 at 25 HIV urban care facilities. Patient information collected at presentation for HIV care included age, sex, WHO clinical stage and screening context. We used 2 definitions of late presentation: the WHO definition of advanced HIV disease (WHO stage 3/4 or CD4 cell count < 200 cells/mm3) and a more inclusive definition (WHO stage 3/4 or CD4 cell count < 350 cells/mm3). Results A total of 10,137 HIV-infected individuals were included in the analysis. The median age was 40 years; 68% were female. A total of 45.9% or 47.5% of the patients were late presenters, depending on the definition used. The percentage of patients with late presentation (defined as WHO stage 3/4 or CD4 cell count < 350 cells/mm3) decreased during recent years, from 70.7% in 2013 to 46.5% in 2017 and 23.4% in 2020. Age was associated with a significantly higher risk of LP (p < 0.0001). We did not observe any impact of sex. Conclusions The frequency of late presentation for care is decreasing in Kinshasa, DRC. Efforts have to be continued. In particular, the issue of late diagnosis in older individuals should be addressed.